Effectiveness of using Scrapbook Media on Learning Outcomes of Fine Arts Students Class VIII SMP Negeri 2 Barant - Maharani Putri Arum; Abd Kahar; Muhammad Takdir (MultiTech Publisher, 2024)
The Scrapbook media comes from the English